SUITABILITY AND CARRYING CAPACITY ANALYSIS OF MANGROVE AND COASTAL ECOTOURISM AREAS ON UNTUNG JAVA ISLAND - Rabiyanti I.; Lubis F. R.; Afridiani F.; Anjasmoro A.; Akbar D. R.; Wahid A.; Nugroho F. A.; Franciscus E. (Universitas Mataram, 2026)
Untung Java Island is one of the islands located within the Kepulauan Seribu archipelago. with significant coastal resource potential. This study aims to assess the suitability level and carrying capacity of mangrove and beach ecotourism areas on Untung Java Island. Data were collected using a 10x10 m quadrat transect method, water quality measurements, and analysis of the Tourism Suitability Index and Area Carrying Capacity. The study shows that the mangrove ecosystem is classified as “Not Suitable” for ecotourism activities. In contrast, the beach ecosystem shows different results, with Arsa Beach categorized as “Suitable” (TSI = 2.236) and Sakura Beach as “Highly Suitable” (TSI = 2.615). The carrying capacity analysis indicates values of 16 people/day at Sakura Beach and 12 people/day at Arsa Beach. The results emphasize the need for carrying capacity-based management to ensure sustainable ecotourism development.